DETERMINATION OF FOLATE RETENTION DURING TOFU PREPARATION USING TRIENZYME TREATMENT AND MICROBIOLOGICAL ASSAY - Ginting, Erliana; Arcot, Jayashree; Chox, Julian M. (Indonesian Journal of Agricultural Science, 2003)
Megaloblastic anaemia, neural tube defects, coronary heart disease, and some forms of cancer have been linked to an inadequate dietary intake of folate. Legumes are good sources of folate, however, processing may affect folate availability in legume foods. This study investigated the folate content and retention during the preparation of tofu through the trienzyme treatment (protease, Î±-amylase, and human plasma) and microbiological assay using Lactobacillus casei. The results showed that the total folate content was considerably reduced during tofu preparation, from 273.4 Âµg 100 g-1 dwb in soybean seed to 108.4 Âµg 100 g-1 dwb in tofu, yielding a folate retentionof 40%. Folate losses were mainly due to leaching into the water during soaking and pressing as well as heat destruction during milling and boiling. High folate loss (51%) was particularly found in the whey. A shorter soaking time (8 hours), optimum extraction, and pressing methods were suggested with respect to minimizing folate losses during tofu preparation. This studysuggests that the consumption of 100 g of deep-fried tofu may satisfy 21% of the recommended dietary intake (RDI).